Study of Optimal Replacement of Thyroxine in the Elderly (SORTED) – results from the feasibility randomised controlled trial. Issue 1 (December 2016) - Razvi, Salman; Ingoe, Lorna; Ryan, Vicky; Pearce, Simon; Wilkes, Scott
Abstract Background Hypothyroidism is a common condition, particularly in the older population. Thyroid hormone requirements change with age and serum TSH levels also alter, especially in older patients. However, in practice laboratory reference ranges for thyroid function are not age-specific and treatment in older patients aims to achieve a similar target thyroid function level as younger age groups. Methods A dual centre, single blind, randomised controlled trial was conducted to determine the feasibility of a future definitive RCT in hypothyroid individuals aged 80 years or older who were treated with levothyroxine. Potential participants were identified from 17 research-active GP practices (n  = 377), by opportunistic invitations (n  = 9) or in response to publicity (n  = 4). Participants were randomly allocated to either usual (0.4–4.0 mU/L) or a higher (4.1–8.0 mU/L) target serum TSH range. Information on participants' willingness to enter the trial, acceptability of study design, length of time to complete recruitment and dose titration strategy was collected. Results Fifteen percent (57/390) of potentially eligible hypothyroid individuals consented to participate in this trial and 48 were randomised to trial medication for 24 weeks, giving a recruitment rate of 12 %. Recruitment averaged 5.5 participants per month over approximately 9 months. Eight participants withdrew (3/24 and 5/24 in the usual and higher TSH arms, respectively) with the commonest reason cited (5 patients) being tiredness. Interestingly, 3/5 participants withdrew from the site that required a visit to a Research Facility whereas only 5/43 participants withdrew from the site that offered home visits. In the higher TSH arm, of those participants who completed the study, approximately half of participants (10/19) reached target TSH. Conclusions It is feasible to perform a randomised controlled trial of thyroid hormones in hypothyroid patients aged 80 or older. A definitive trial would require collaboration with a large number of General Practices and the provision of home visits to achieve recruitment to time and target. Power calculations should take into account that approximately 12 % of those approached will be randomised and 1 in 6 participants are likely to withdraw from the study. Finally, several dose adjustments may be required to achieve target serum TSH levels in this age group. Trial registration ISRCTN Number:16043724 Registered 22 June 2012 Clinicaltrial.gov Number: NCT01647750 EudraCT Number: 2011-004425-27